Trichoplax adhaerens reveals a network of nuclear receptors sensitive to 9-cis-retinoic acid at the base of metazoan evolution - Novotný, Jan Philipp; Chughtai, Ahmed Ali; Kostrouchová, Markéta; Kostrouchová, Veronika; Kostrouch, David; Kaššák, Filip; Kaňa, Radek; Schierwater, Bernd; Kostrouchová, Marta; Kostrouch, Zdenek (PeerJ, 2017)
Trichoplax adhaerens, the only known species of Placozoa is likely to be closely related to an early metazoan that preceded branching of Cnidaria and Bilateria. This animal species is surprisingly well adapted to free life in the World Ocean inhabiting tidal costal zones of oceans and seas with warm to moderate temperatures and shallow waters. The genome of T. adhaerens (sp. Grell) includes four nuclear receptors, namely orthologue of RXR (NR2B), HNF4 (NR2A), COUP-TF (NR2F) and ERR (NR3B) that show a high degree of similarity with human orthologues. In the case of RXR, the sequence identity to human RXR alpha reaches 81% in the DNA binding domain and 70% in the ligand binding domain. We show that T. adhaerens RXR (TaRXR) binds 9-cis retinoic acid (9-cis-RA) with high affinity, as well as high specificity and that exposure of T. adhaerens to 9-cis-RA regulates the expression of the putative T. adhaerens orthologue of vertebrate L-malate-NADP+ oxidoreductase (EC 1.1.1.40) which in vertebrates is regulated by a heterodimer of RXR and thyroid hormone receptor. Treatment by 9-cis-RA alters the relative expression profile of T. adhaerens nuclear receptors, suggesting the existence of natural ligands. Keeping with this, algal food composition has a profound effect on T. adhaerens growth and appearance. We show that nanomolar concentrations of 9-cis-RA interfere with T. adhaerens growth response to specific algal food and causes growth arrest. Our results uncover an endocrine-like network of nuclear receptors sensitive to 9-cis-RA in T. adhaerens and support the existence of a ligand-sensitive network of nuclear receptors at the base of metazoan evolution.
Keywords: HNF4; Nuclear receptor; COUP; Trichoplax adhaerens; ERR; Food; 9-cis retinoic acid; RXR